Tolerance induction to clotting factors with monoclonal antibodies - Graca, Luis (Henry Stewart Talks, 2020)
The immunogenicity of foreign tissues and proteins, Induction of immune tolerance with monoclonal antibodies, Properties of therapeutic immune tolerance, The challenges to achieve tolerance to clotting factors in hemophilia, The importance of appropriate antigen presentation for effective immune tolerance induction, Cellular and molecular mechanisms underlying immune tolerance: IL-10, Foxp3, regulatory T cells, and T cell depletion, Different routes of antigen presentation can recruit different tolerance mechanisms